2011
DOI: 10.2463/mrms.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RF Heating due to Various Implants during MR Procedures

Abstract: We evaluated radiofrequency (RF) heating of various implants embedded in a gel phantom during magnetic resonance (MR) procedures. We examined the dependence of RF heating on variation in speciˆc absorption rate (SAR) and angle between the implant and the static magneticˆeld (B 0 ) and on the displacement of the phantom in the irradiation coil using a 1.5-tesla MR system, and we compared the in‰uence of RF heating on the same implant using a 3.0T MR system.Our results support the occurrence of RF heating of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 26 publications
5
36
1
Order By: Relevance
“…RF heating of cobalt-chromium alloy implants and titanium alloy implants was evaluated in vitro by Muranaka. The maximum temperature rise of titanium implant was lower compared with cobalt-chromium [33,39]. Our results indicate that, under lower dose microwave irradiation (20 w-40 w), the temperature increase of muscles adjacent to titanium alloy implants was lower than 43°C.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…RF heating of cobalt-chromium alloy implants and titanium alloy implants was evaluated in vitro by Muranaka. The maximum temperature rise of titanium implant was lower compared with cobalt-chromium [33,39]. Our results indicate that, under lower dose microwave irradiation (20 w-40 w), the temperature increase of muscles adjacent to titanium alloy implants was lower than 43°C.…”
Section: Discussionmentioning
confidence: 78%
“…In the case of implants with thin or sharp edges, electromagnetic field lines are focused along the edge or an end, leading to a high local flux [33], resulting in significant increase in absorption and temperature in tissues. In this study, no significant difference in temperature rise was observed between the ends and the middle part of the implants, due to the small size and good thermal conductivity of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RF heating of cobalt-chromium alloy implants and titanium alloy implants was evaluated in vitro by Muranaka. The maximum temperature rise for titanium implant was obviously lower than that for cobalt-chromium [35,40]. Hence, the current study was based on the assumption that there is no dramatic temperature raise in tissues around titanium alloy implants resulting from a low dose microwave exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of thermal effects in MRI depends on numerous factors, such as the magnetic properties of the metal, size and shape of the metallic body, the position of the body relative to the static magnetic field (B 0 ), and specific absorption rate (SAR). Latter in turn differs between MR field‐strengths . In a number of studies it was shown that the local temperature rise can exceed 5°C .…”
Section: Introductionmentioning
confidence: 99%